199k views
3 votes
For each equation below, solve for x.

a) 3 (x-1) = 2x - 3 + 3x


b) 4x + 1/3 = x - 5/2


c) 1/2x - 17 = -23

For each equation below, solve for x. a) 3 (x-1) = 2x - 3 + 3x b) 4x + 1/3 = x - 5/2 c-example-1
User Makle
by
4.9k points

1 Answer

4 votes
(a) 3(x-1) = 2x-3+3x
3x-3 = 5x-3
3x-5x = 0
-2x =0
x = 0

(b) 4x +1/3 = x - 5/2
4x-x = -5/2-1/3
3x = -17/6
x = -17/6 . 1/3
x = - 17/18
(c) 1/2 x - 17 = -23
1/2 x = -6
x = -6.2
x = - 12
User Marton Trencseni
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.